Intraocular nematode and other parasites associated with Physalaemus albonotatus (Anura: Leptodactylidae) from Corrientes, Argentina - Gonzalez, Cynthya Elizabeth (2019)
In this study, we report three novel parasites in a Physalaemus albonotatus collected in Corrientes (Argentina), a nematode larva of the order Rhabditida in the eye, and cystacanths and cosmocercids in the mesentery and the large intestine, respectively. We highlight that this study reports for the first time the accidental presence of Rhabditid nematodes naturally infecting the eye of a species of anuran.